Geschwind Syndrome in frontotemporal lobar degeneration: Neuroanatomical and neuropsychological features over 9 years. (September 2017) - Veronelli, Laura; Makaretz, Sara J.; Quimby, Megan; Dickerson, Bradford C.; Collins, Jessica A.
Abstract: Geschwind Syndrome, a characteristic behavioral syndrome frequently described in patients affected by temporal lobe epilepsy (TLE), consists of the following features: hyper-religiosity, hypergraphia, hyposexuality, and irritability. Here we report the 9-year-clinical course of a case of Geschwind Syndrome that developed as a first and salient clinical expression of right temporal lobe variant of frontotemporal lobar degeneration (FTLD). Only one patient affected by frontotemporal dementia has previously been shown to present with Geschwind Syndrome. MS presented at age 73 with 3 years of personality and behavioral symptoms. Her early symptoms primarily included hyper-religiosity, hypergraphia, and poor emotional regulation (irritability, impulsivity, disinhibition, egocentric behavior). Over nine years, other cognitive functions (word retrieval, memory coding and recall, set-shifting, famous face and building recognition) became affected; however, hyper-religiosity, hypergraphia, and scarce emotional control remained her most prominent deficits. Longitudinal cortical thickness and volumetric analyses revealed early atrophy in the right temporal pole, right amygdala, and right hippocampus, which progressively affected homologous regions in the left hemisphere. The present case describes an unusual clinical picture associated with frontotemporal dementia (FTD), in which the most salient symptoms originated and remained consistent with Geschwind Syndrome.